Education for Early Childhood is Post-disaster - Mardyawati; Badruddin (Simposium Antar Bangsa Seminar dan Workshop)
This paper aims to analyze how to deal with Education for Early Childhoodafter adisaster. Writing this article uses field research methods next to the library by taking a sample comparison in locations that have been affected by the disaster in South Sulawesi. The Act 20, 2003 on The National Education System of Indonesia set in Chapter I, Section 1, Paragraph 14 that The ECE is a development fforts aimed at children from birth to age six, through the provision of educational stimulus to help the growth and development of children physically and mentally so that Childhood have the readiness to enter the further education.Basic of Study on the Act No. 20 of 2003 on National Education System Chapter VI Seventh Section Article 28 paragraph (2) early childhood education is conducted througheducational institution both formal and non formal institutions and informalinstitutions.The Act 23, 2002 on The concerning Protection of Children Chapter III Section 9 paragraph 1 which stipulates that: Every child has the right to obtain education and teaching in the framework of his personal development and the level of his intelligence in accordance with his interests and talents.The results of the study indicate that the impact of disasters on early childhood provides deep trauma so that it requires recovery through education that is appropriate to the needs of the child early age.Education for early childhood after a disaster requires its own method because not only will knowledge be given but trauma recovery that needs special handling, thus the effort to guide early childhoodaffected by disasters is to use the principle of learning while playing and playing while studying. In line with the laws of the Republic of Indonesia that consciously on early child needs to be done pendid iright through the provision of educational stimulation to help the growth and development of the soul and the mind and physical child.